OUTCOMES AND MORTALITY IN PATIENTS ADMITTED FOR ACUTE CORONARY SYNDROME WITH PSORIATIC ARTHRITIS - Karla Inestroza, MD (Elsevier, 2024)
Therapeutic Area: ASCVD/CVD in Special Populations Background: There is evidence that patients with psoriatic arthritis (PsA) have a higher risk of cardiovascular disease (CVD) than the general population. Both conventional and non-conventional risk factors contribute to the increased cardiovascular (CV) risk, and inflammation plays an essential role in the pathogenesis of atherosclerosis in this population.In this large retrospective study, we aimed to compare the outcomes of patients admitted for acute coronary syndrome (ACS) with PsA versus matched controls. Methods: The National Inpatient Database was queried from 2011 to 2019 for relevant ICD-9 and -10 diagnostic and procedural codes. We identified patients admitted with ACS with a concomitant diagnosis of PsA. We excluded those with type 1 DM, rheumatoid arthritis, gout, lupus, scleroderma, and ankylosing spondylitis. We identified 2,526 patients with PsA and matched them in a 2:1 ratio for age, sex, and gender with patients without PsA (n=5,026). Results: Those patients admitted with ACS and PsA had a higher prevalence of hyperlipidemia, obesity, obstructive sleep apnea, alcohol use, coronary artery disease, and liver disease than those without PsA. Those without PsA had a higher prevalence of tobacco use, substance use, chronic kidney disease, chronic obstructive pulmonary disease, and a history of prior stroke than those with PsA.Regarding outcomes after multivariate logistic regression, those patients admitted with ACS and PsA had higher rates of 2nd-degree AV Block and percutaneous coronary intervention. Conversely, those admitted with ACS without PSA had higher all-cause mortality, cardiac arrest, acute heart failure, cardiogenic shock, acute kidney injury, and sepsis compared to those with PsA. Conclusions: In this national retrospective study, patients admitted with ACS and PsA had lower all-cause mortality and fewer complications than those without PsA. However, this analysis could not stratify PsA by severity or date of onset, which might significantly influence the results. Further studies on patients with moderate to severe PsA can help elucidate the effect of inflammation on outcomes after ACS in this population.